NEUROMARKETING – THE ART OF CAPTURING THE CONSUMER'S MIND AND EMOTIONS (European Journal of Economics, Finance and Business Development, 2025)
This article analyzes the concept of neuromarketing, its role in marketing strategies, and methods of influencing consumer consciousness. It explores opportunities to enhance brand and advertising effectiveness through technologies developed on the basis of neurobiological research.